2013
DOI: 10.4018/ijcallt.2013100102
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Learn Digitally

Abstract: How can educators empower and encourage their students to be more proactive, and give them the tools necessary to learn on their own, utilizing digital language learning resources in a culturally sensitive way? Described below is a project that introduced students to how technology and the Internet can empower the independent language learner. The goal was for the students to develop knowledge of and confidence in self-instruction and learn how to use technology and the Internet to further their language educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…We argued that it is an affordance of online communication that inexperienced Internet users who were new to distance education were able to form such a community, and crucially were able to collectively negotiate their own language practices against those of the native speakers. The idea of a community developing their own norms of language use may go against stereotypically rigid conceptions of exo-normative language learning, but we can strongly argue that such norm-setting practices build and sustain communities of practice, and crucially from a pedagogical perspective, promote individual learner autonomy (as Nguyen, 2010;Nguyen & White, C. (2011);Terhune, 2013;and White, J. R., 2015b have explicitly argued). An additional important methodological argument we have made is that it is possible to study norm-setting in limited shorttimeframe data sets.…”
Section: Discussionmentioning
confidence: 99%
“…We argued that it is an affordance of online communication that inexperienced Internet users who were new to distance education were able to form such a community, and crucially were able to collectively negotiate their own language practices against those of the native speakers. The idea of a community developing their own norms of language use may go against stereotypically rigid conceptions of exo-normative language learning, but we can strongly argue that such norm-setting practices build and sustain communities of practice, and crucially from a pedagogical perspective, promote individual learner autonomy (as Nguyen, 2010;Nguyen & White, C. (2011);Terhune, 2013;and White, J. R., 2015b have explicitly argued). An additional important methodological argument we have made is that it is possible to study norm-setting in limited shorttimeframe data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have particularly shown that CALL helps to develop autonomy in language learning, through social network tools such as wikis (Kessler & Bikowski, 2010), collaborative digital technology (Hafner & Miller, 2011), and instructional support (Terhune, 2013).…”
Section: Introductionmentioning
confidence: 99%